Edukasi Pencegahan ISPA pada Anak Oleh Keluarga di Puskesmas Simpang Kawat Kota Jambi - Armina Armina (Jurnal Abdimas Kesehatan (JAK), 2023)
Acute Respiratory Infection (ARI) is a common disease with mild to severe manifestations. Symptoms include fever, cough, and often sore throat, runny nose. ARI usually lasts more than 14 days. Puskesmas Simpang Kawat Jambi City experienced an increase in cases of Acute Respiratory Infection (ARI) in children in August-September 2022 as many as 20-25 cases per month. The purpose of this service is to educate the prevention of children's ARI in families. The methods in this community service are lectures, demonstrations and leaflets. The time of community service was held on December 22, 2022. Participants followed the community service with enthusiasm which was attended by 14 participants and at the end of the material evaluation there were 10 participants. The results of the community service increased knowledge where 5 participants could answer 5 question items, namely the definition of ARI in children, the causes of ARI, 5 out of 9 signs of symptoms of children's ARI, 4 out of 6 prevention of ARI in children, and 4 out of 11 ARI treatments in children while at the beginning of education 3 participants knew the definition of ARI, 3 participants knew the cause of ARI from germs, 3 participants knew the symptoms of ARI were only cough and cold, 3 participants knew the prevention of ARI by wearing masks, 2 participants knew the treatment of ARI by taking cough and cold medicine. The results of this community service are expected to be applied in the form of providing information in the form of education and demonstrations on a scheduled basis so that family knowledge is increasing.